PENGEMBANGAN E-MODUL FISIKA BERBASIS PROBLEM BASED LEARNING MENGGUNAKAN GOOGLE SITES PADA MATERI GELOMBANG CAHAYA - Aini, Hikmah; Purwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a Problem-Based Learning (PBL)-based physics e-module using Google Sites on the topic of light waves. The background of this study is based on students’ difficulties in understanding physics lessons, low student learning outcomes, and physics instruction that is dominated by conventional, teacher-centered methods. The research method used is Research and Development (R&D) employing the ADDIE model. The research subjects involved 30 students from Class XI-K2 at SMA Negeri 1 Deli Tua, subject matter experts, media experts, instrument experts, and a physics teacher. Data were collected through observation, interviews, questionnaires, and student achievement tests. The research results indicate that the developed e-module received a “highly feasible” rating, with a 94.90% approval rate from content experts and 92.67% from media experts. A practicality test conducted through a limited trial showed a percentage of 94.20% in the “very practical” category, while a large-scale trial showed a percentage of 95.90% among students and 96% among teachers. The effectiveness of the e-module was assessed based on improvements in student learning outcomes. The average pre-test score was 61.33, while the average post-test score after using the e-module increased to 85.33. The analysis results showed an improvement in learning outcomes with an N-Gain score of 0.62, which falls into the moderate category. Thus, the developed e-module is effective in improving student learning outcomes on the topic of light waves.